Real estate market activity in Slovenia in 2000-2006 - Tomaž Grilj; Anka Lisec; Samo Drobne (Geodetski Vestnik, 2009)
This paper examines a particular aspect of Slovenian real estate market that is still developing –real estate market activity. Only two decades ago, Slovenia still had a socialist, planned economy, so there is a lack of tradition in the fields of both the real estate market and analysis of that market. The former only started to develop with the transition to the market-oriented economy in the beginning of the 1990s. Significant progress was observed in the second half of the 1990s, due to the favourable economic development of the country. In our research, we focused on the real estate market development in the 2000-2006 period, which was marked by major changes in legislation and other institutional backgrounds, directly or indirectly referring to the field of real estate and real property. The development of the real estate market in Slovenia was examined for a given period on the basis of the available market data, which have been acquired from the Tax Administration of the Republic of Slovenia; the real estate market activity development is analysed by statistical regions and types of real estate. The results show general developments in the Slovenian real estate market for the given period and, in particular, the influence of institutional and legal factors on real estate market activity.